Physical Education and Physical Activity Within a Whole School, Whole Community, Whole Child Approach. Issue 2 (12th February 2022) - Dauenhauer, Brian; Stoepker, Peter
Abstract: The purpose of this article is to introduce the Comprehensive School Physical Activity Program (CSPAP) model as the physical education (PE) and physical activity (PA) component of the Whole School, Whole Community, Whole Child (WSCC) model. CSPAP consists of five core elements including quality PE, PA during school, PA before/after school, staff involvement, and family & community engagement, with quality PE serving as the cornerstone. There are extensive resources to support the implementation of CSPAP in schools from organizations such as the Centers for Disease Control and Prevention (CDC), Springboard to Active Schools, and SHAPE America – Society of Health and Physical Educators. Health and physical education (HPE) professionals interested in promoting PE and PA in schools should focus on four main strategies: (1) ensure quality PE, (2) follow the steps in the CDC's CSPAP Guide, (3) advocate for PE and PA at the school, district, and state levels, and (4) participate in continuing professional development related to the five components of CSPAP. For physical education teacher education (PETE) programs wishing to support CSPAP, it is essential to first develop high quality PE teachers. Then, they can consider a variety of strategies for extending preservice teacher learning to other school PA opportunities through integrated coursework and alternative field experiences. One key to successful CSPAP implementation is collaboration with community members outside of the school, including universities. The article concludes with a hypothetical example of how a school could integrate the strategies outlined here.